SEROPREVALENCIA DE VIRUS NEUMOPATÓGENOS EN ALPACAS ADULTAS DE LA PROVINCIA DE CANCHIS, CUSCO - Victorio C., Willy (2004)
The objective of the present study was to determine the presence of respiratory viruses in the alpaca population of Canchis province, Cusco. Viral neutralization tests, utilizing secondary cellular cultures of bovine origin and cytopathic virus, were used to detect neutralizing antibodies against PI-3, BHV1, and BRSV in a total of 345 serum samples from 31 small farms. All the farms had seroreactive animals for BRSV and PI-3, but only one animal was seroreactive to BHV1. The seroprevalence against BRSV and PI-3 was 80.2 ± 7.0% (101/126) and 67.5 ± 4.9% (233/345) respectively. The results suggest that these animals have been exposed to respiratory viruses were undergoing active viral replication at the time of sampling.